Arctic and Atlantic Waters in the Norwegian Basin, Between Year Variability and Potential Ecosystem Implications - Skagseth, Øystein; Broms, Cecilie; Gundersen, Kjell; Hátún, Hjálmar; Kristiansen, Inga; Larsen, Karin Margretha H.; Mork, Kjell Arne; Petursdottir, Hildur; Søiland, Henrik (Frontiers in Marine Science, 2022)
The ocean climate of the southern Norwegian Sea - the Norwegian Basin - is largely set by the relative amount of Atlantic Water in the eastern and Arctic Water in the western region. Here we utilized hydrographic data from repeated sections, together with annually gridded survey data of the upper 1000 m, to resolve the main hydrographic changes over the period 1995-2019. Based on integrated heat -and freshwater content, we divide into three periods. The period 1995-2005 we denote as “Arctic” and it is characterized by relative fresh and cold Atlantic Water overlaying Arctic Intermediate Water that basically cover the whole Norwegian Basin. Differently, during the period 2006-2016 the Atlantic Water is warmer and more saline, and the extent and thickness of Arctic Intermediate Water is greatly reduced. During the recent years, 2017-2019, there has been a major freshening of the Atlantic Waters, the layer of Arctic Intermediate Water has not recovered, but instead a layer of warmer but relative fresh Arctic Water has expanded. We find that increasing abundance of the Arctic zooplankton, Calanus hyperboreus, into the southern and eastern Norwegian Basin coincide with increased extent of Arctic Water. We note that the overall mesozooplankton biomass in the Norwegian Basin is significantly higher in periods of relative high amount of “Arctic” Water. Furthermore, we show that both nitrate and silicate winter (pre-bloom) concentrations are significantly higher in the Arctic Water compared to Atlantic Water, and that there is a reduction in nutrients from the “Arctic” period 1995-2005 compared to the “Atlantic” period 2006-2016. Since these nutrients can be interpreted as the potential for new production, changes in the influx of western subarctic waters are expected to have a bottom-up effect on the Norwegian Sea. Hence, this study indicates that rather than the temperature of the Atlantic Waters, the amount of Arctic Waters and their concentration of nutrients and zooplankton, is more important for the ecosystem functioning.